U-shaped assembly line balancing with Grouping Evolution Strategy (GES) - Davani, Pouria Pourmomen (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
In this research, we have applied Grouping Evolution Strategies (GES) as an alternative solution to U-shaped assembly line balancing problem (UALBP). By introduction of just-in-time (JIT) production principle, it can be proven that U-shaped assembly line system has better performance than its predecessor traditional straight line system. The parameters to compare are the number of workstations (the line efficiency) and the smoothness index of workload. Our evaluation shows by applying GES, at least same line efficiency of workstation integration can be achieved. Moreover, the variation and smoothness index of workload have been improved. Moreover, to measure the performance validation of the proposed algorithm, a number of standard UALBPs in the literature were used to compare the proposed algorithm results with other related work results. Simulation results show that the proposed model produced as good or even better line efficiency of workstation integration and improved the variation and smoothness index of workload. Keywords: U-shaped assembly line balancing, Grouping Evolution Strategies, Workstation, Smoothness Index

ÖZ : Bu araştırmada U-sekilli montaj hattı dengeleme problemine (U-shaped assembly line balancing problem - UALBP) alternatif bir çözüm olarak evrim stratejilerini gruplama sistemini (Grouping Evolution Strategies -GES) uyguladık. Zamanında üretim prensibi kuramına göre (just-in-time JIT) U-şekilli montaj hattı sisteminin performansı geleneksel düz çizgi sisteminden daha iyi olduğ ispatlanmıştır. Performans ölçümünde karşılaştırılan parameteler ise, iş istasyonlarının sayısı ve iş yükü pürüzsüzlük indeksi (hat verimliliği)’dir. Değerlendirmelerimiz göstermiştir ki, belirtilen probleme GES uygulanarak istenilen iş iştasyonu entegrasyon hat verimliliği elde edilmiştir. Buna ek olarak iş yükü pürüzsüzlük indeksi de geliştirilmiştir. Ayrıca önerilen algoritmanın performans doğrulamasını ölçmek için, literatürde bulunan bir dizi standart UALBP’ler kullanılarak önerilen algoritma sonuçları diğer ilgili çalışmalarla karşılaştırılmıştır. Simulasyon sonuçları göstermiştir ki, önerilen model, iş iştasyonu entegrasyon hat verimliliğin ölçümünde daha iyi sonuç vermiş ve iş yükü değişimi ve pürüzsüzlük indeksini de iyileştirmiştir. Anahtar Kelimeler: U-sekilli montaj hattı dengeleme (UALB), gruplama evrim stratejileri (GES), iş istasyonu (workstation), pürüzsüzlük indeksi (smoothness index)
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2015. Supervisor: Assist. Prof. Dr. Gürcü Öz.
Keywords: Computer Engineering; Assembly-line methods; U-shaped assembly line balancing; Grouping Evolution Strategies; Workstation; Smoothness Index